Haematic Mummification in a Mare With Twin Pregnancy - Pizzigatti, Dietrich [UNESP]; Batista, Fernando Arevalo; Martins, Charles Ferreira; Mueller, Thiago Rinaldi [UNESP]; Hussni, Carlos Alberto [UNESP] (Elsevier B.V., 2012)
Mummification occurs when the fetus dies during the second or third trimester of gestation and remains in the uterine cavity because of the persistence of the corpus luteum or existence of another live fetus. Generally, the mummified fetus and fetal membranes undergo desiccation. The hematic process is similar, but the fetus appears like melted chocolate and becomes lodged between the uterus and chorion. This report describes the treatment of dystocia in a mare with twin pregnancy, with one fetus having undergone hematic mummification. Although difficult to diagnose, the possibility of a second fetus should be investigated in mares with dystocia. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Mummification; Hematic; Equine; Twin